Sport and Disability 2018
DOI: 10.4324/9780429505317-9
|View full text |Cite
|
Sign up to set email alerts
|

The fiddle of using the Paralympic Games as a vehicle for expanding [dis]ability sport participation

Abstract: In this paper we highlight the need to explore the excessive significance given to the Paralympic Games as a vehicle for the encouragement of participation of people with a disability within sport. The media spectacle around the games that the International Paralympic Committee (IPC) has worked tirelessly to develop has become, for policy makers and the public alike, a sufficient outlet for disability sport provision. We argue that the honourable goals of the IPC articulated through the ethos of Paralympism ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 1 publication
0
19
0
2
Order By: Relevance
“…"British Paralympians' success in 2012 brought celebrity status but has done little for the daily life of the disability community" 1 . This assertion is hardly surprising despite claims made by the International Paralympic Committee (IPC) regarding the empowering potential of sport they largely have been unsubstantiated ( [2][3][4] ). It is, of course, extremely difficult to evaluate to what extent sport events ignite social change, let alone the potential of empowerment, due to both conceptual and methodological weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…"British Paralympians' success in 2012 brought celebrity status but has done little for the daily life of the disability community" 1 . This assertion is hardly surprising despite claims made by the International Paralympic Committee (IPC) regarding the empowering potential of sport they largely have been unsubstantiated ( [2][3][4] ). It is, of course, extremely difficult to evaluate to what extent sport events ignite social change, let alone the potential of empowerment, due to both conceptual and methodological weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…This provided a sense of structure to their coaching reality and brought with it significant symbolic capital. This clear alignment to the doxic structure further reinforced the social divisions between ‘ability-disability’ (Howe and Silva, 2016). That is, for the athletes, social structure and power were determining of identity and not individual autonomy.…”
Section: Analysis and Discussionmentioning
confidence: 78%
“…It has been suggested that sport provides a context that can challenge and influence the social and cultural perceptions of disability and disabled people (Howe and Silva, 2016). This is reinforced by binaries that often frame discussions about Paralympic and disability sport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But on the hand, once the host organization disbands after completion of the Games, the social legacy in terms of improving access to the local environments is limited at best. Indeed, as argued by former Paralympians themselves, whilst the Paralympics brings some benefits, it can also counterproductive to the lives of disabled people beyond sport (Braye 2016;Howe & Silva, 2018;Peers, 2012). Such points raise issues not only about the claims sport organisations make.…”
mentioning
confidence: 99%